First Molecular Detection of Mycobacterium ulcerans pseudoshottsii From Gulf Strain Striped Bass ( Morone saxatilis ) - Alex W. Rakestraw; Kayla M. Fast; Magdalene Dogbe; Sophie Picq; Joseph P. Receveur; Christine Chevillon; Jean‐François Guégan; Jennifer L. Pechal; Heather R. Jordan; M. Eric Benbow; Michael W. Sandel (Journal of Fish Diseases, 2026)
Mycobacterium ulcerans pseudoshottsii is a mycolactone‐producing bacterium previously isolated from Striped Bass ( Morone saxatilis (Walbaum)) from Chesapeake Bay and adjacent waters of the Atlantic Coast of North America. We report the first molecular detection of this pathogen in the native Gulf strain of Morone saxatilis collected from the Pearl River, Mississippi (USA). Molecular identification was conducted using a novel PCR assay targeting the parA‐625 intergenic spacer of the virulence‐associated pMUM plasmid. The isolate was unambiguously assigned to M. u. pseudoshottsii based on diagnostic single nucleotide polymorphisms (SNPs) and phylogenetic analysis. This report expands the known range of M. u. pseudoshottsii to include Gulf Coast watersheds and highlights the need for enhanced surveillance in wild and aquacultured fish populations of the southern United States.

Sink or swim: Phylogenomic analysis of Baikal sculpins reveals multiple transformations to pelagic, bathybenthic, and lotic ecomorphologies - Michael W. Sandel; Andres Aguilar; Sergei Kirilchik; David A. Neely; Bakhtiar E. Bogdanov; Kayla M. Fast; Joshua D. Millwood (Molecular Phylogenetics and Evolution, 2025)

Conservation genomics of the threatened Trispot Darter (Etheostoma trisella) - Kayla M. Fast; Brook L. Fluker; Bernard R. Kuhajda; Patrick E. O’Neil; Stuart W. McGregor; Matthew S. Piteo; Michael W. Sandel (Conservation Genetics, 2024)